NATO and Burden-Sharing: NATO Membership Widely Supported, but Increased Defense Efforts Broadly Opposed. - United States Information Agency. Office of Research.; Wertman, Douglas A. (Tufts University. Tisch Library., 2019)
This is one of several reports based on USIA-commissioned surveys of public opinion in Britain, West Germany, Italy, Belgium, the Netherlands, Denmark and Norway between late May and early July 1984. Each survey comprised 900 to 1200 personal interviews representative of the national population 18 and over. Earlier surveys, sponsored by USIA and other organizations, are used for trend comparisons.; Tisch Library copy is missing page 2.; Research Memorandum M-9/11/84